Human sciences students’ perception of an Arabic course and their retention of the language - Lotfie, Maskanah Mohammad; Zubir, Badri Najib; Md Ghalib, Mohd. Feham (2012)
The incorporation of Arabic in Human Sciences (HS) undergraduate curricula is one of the manifestations of the International Islamic University Malaysia’s vision of continuously Islamizing knowledge. HS undergraduates have to learn the language up to the intermediate level. The requirement, though theoretically a sound means to assist the University to achieve its mission, has caused mixed responses with regard to its usefulness and varying degrees of acceptance among the students, the majority of whom speak Malay as their mother tongue. Thus, the main purpose of this study is to investigate the extent to which the Arabic for HS students programme is beneficial to the learners who spend up to six semesters learning the language. Specifically, it investigates learners’ perception of a course and whether the learners retain knowledge of the language attained at the end of the course.